Crushed limestone from Pila Spi Formation as alternative for conventional aggregate, Qaradagh area, Kurdistan region - Iraq - Hama, Hawkar O.; Ahmed, Hazhar H.; Majid, Razbar F.; Omer, Nyan T. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The late Eocene limestone rocks of Pila Spi Formation from Qaradagh area in Sulaimani Governorate, Kurdistan region (NE of Iraq) have been selected as alternative for conventional aggregate in concrete. The collected samples from the section are analyzed chemically and physically. Field investigations in the area were adopted. The laboratory tests including particle size analysis, los angeles abrasion, specific gravity, water absorption, soundness and gypsum content had been done for the crushed limestone aggregates. In addition, twelve concrete cubes in dimension 15cm3 have been molded according to the Iraqi Standards and the compressive strength test was carried out on it. The aggregate mix design consists of 1.5: 2: 4 with 0.5 water/ cement ratio. The results of the aggregate are compared with the international standard tests; accordingly, the Limestone of Pila Spi Formation is acceptable as alternative for natural sand and gravel.
Keywords: Pila Spi FormationCrushed limestoneCompressive strength